Characterization and simultaneous quantification of biological aporphine alkaloids in Litsea cubeba by HPLC with hybrid ion trap time‐of‐flight mass spectrometry and HPLC with diode array detection. Issue 15 (3rd July 2015) - Zhang, Shuiying; Zhang, Qian; Guo, Qiang; Zhao, Yunfang; Gao, Xiaoli; Chai, Xingyun; Tu, Pengfei
<x xml:space="preserve">Abstract</x> The root and rhizome of Litsea cubeba (Lour) Pers., named 'Dou‐chi‐jiang' in Chinese, has been traditionally used for treatment of cardiovascular and cerebrovascular diseases, rheumatic arthralgia, and other diseases in China. Aporphine alkaloids are its characteristic ingredients and responsible for its bioactivities, especially anti‐inflammatory and analgesic effects. A sensitive and reliable high‐performance liquid chromatography with diode array detection‐tandem mass spectrometry method was developed for characterization and simultaneous determination of biological aporphine alkaloids in 'Dou‐chi‐jiang'. The optimized chromatographic conditions were performed on an Eclipse XDB C18 column with a gradient of acetonitrile/water containing 0.1% formic acid as the mass spectrometry mobile phase and acetonitrile/water containing 0.2% diethylamine (pH 3.10, adjusted by acetic acid) as the liquid chromatography mobile phase. The fragmentation pathways by loss of CO, ·CH3, ·NH3, and ·NH2CH3 were detected as characteristic for aporphine alkaloids. Based on these characteristics, total 12 analogues were identified. The quantification method was validated in terms of linearity, precision, and accuracy for six major aporphine alkaloids, which was successfully applied for simultaneous determination in ten batches of samples. The established method is simple, rapid, and specific for characterization and quantitation of aporphine alkaloids in 'Dou‐chi‐jiang' and other traditional Chinese medicines rich in this kind of ingredient.